Exploring the Biochemical Profile of Beta vulgaris L.: A Comparative Study of Beetroots and Swiss Chard - Daiana Almeida; Spyridon A. Petropoulos; Tayse F. F. da Silveira; Tânia C. S. P. Pires; Isabel C. F. R. Ferreira; Ângela Fernandes; Lillian Barros (Plants)
In this study, leaves and roots from three beetroot cultivars (cv. Albina Vereduna (white roots), cv. Burpee’s Golden (golden roots), and cv. Pablo F1 (red roots)), as well as Swiss chard leaves (also known as “rhubarb chard”, or Beta vulgaris subsp. cicla var. flavescens) were evaluated in terms of their chemical profile and bioactive properties. Roots were characterized by high carbohydrate content, which also contributed to greater energy values. In contrast, fibers were the predominant macronutrient in leaves, followed by carbohydrates. In both leaves and roots, the most abundant organic acids were quinic and oxalic, while the major free sugar was sucrose. The profile of fatty acid varied between the studied plant parts, with saturated fatty acids prevailing in root samples, while leaves exhibited higher levels of polyunsaturated fatty acids. Regarding phenolic composition, a total of 19 compounds were tentatively identified in leaves (including derivatives of vitexin, isorhamnetin, quercetin, and ferulic, sinapic, and p-coumaric acids), while the roots exhibited a less diverse composition, with a total of eight compounds identified (e.g., derivatives of ferulic, sinapic, p-coumaric and caffeic acids). A total of eight betalains were also identified, out of which seven were classified as betacyanins and one as betaxanthin. The leaves of Swiss chard presented compounds from both classes, while the roots and leaves of cv. Pablo F1 were characterized only by the presence of betacyanins, and those of cv. Burpee’s Golden only by betaxanthin. All samples exhibited relevant activity against Y. enterocolitica, L. monocytogenes, and S. aureus, although leaf samples demonstrated better antioxidant capacity. In conclusion, beetroot leaves outperformed their corresponding roots in terms of chemical composition, antioxidant, and antimicrobial activity, suggesting their high potential as nutrient-rich and functional ingredients in a diverse and well-balanced diet.